Perempuan Berkarir dalam Pandangan Hukum Islam - waty, Fatma (Maqasid: Jurnal Studi Hukum Islam, 2022)
This written Journal goal is for knowing how is Islamic view law, about career woman, where is this era a lot of woman choose double role as house wife as well a career woman. Method of this written is library reaserch by collecting material from same journal, scientific books and holy books, about Islamic law with expectation my this written can be one of woman reference for placing herself.Woman is one of human special being created by Allah, swt., which is destinea as a complementary in man life. As is Allah, swt., created Hawa for accompany Nabiullah Adam runs life and finally develop human being on earth. Woman in jahiliyah period just made it as a second group after men folk in ancient times, a father feith embarrased if he had a girl because there were presumption that a girl is family disgrace. Then Allah, swt., delegated Rasulullah, saw., to lift female degree. In the present, women are not longer censidered as a weak creatures, even women have been equal part with man in terms of work and ability, but it is not necessarily make women have to get out of her line nature. As a special human being who will get the title of mother and wife later, Islam is greatly appreciated women with no restriction if a woman wants to be a cereer, however Islam is not regulating everithing, so that there is a balance between obligation and right for a woman.